Synthesis, Microstructural, and Mechano-Tribological Properties of Self-Lubricating W-S-C(H) Thin Films Deposited by Different RF Magnetron Sputtering Procedures - Vuchkov, Todor (2020)
Carbon-alloyed transition metal dichalcogenide (TMD) coatings have great potential for providing a good tribological response in diverse operating environments. There are di erent ways to synthesize these coatings by magnetron sputtering, with no clear indication of the best possible route for potential upscaling. In this study, tungsten-sulfur-carbon (W-S-C) coatings were deposited by radio frequency (RF) magnetron sputtering via four di erent methods. All coatings were sub-stoichiometric in terms of the S/Wratio, with the bombardment of the growing film with backscattered Ar neutrals being the main mechanism governing the S/Wratio. The crystallinity of the films was dependent on the C and S contents. X-ray photoelectron spectroscopy (XPS) revealed W-S and W-C bonding in all coatings. Raman spectroscopy showed the presence of an a-C phase with predominant sp2 bonding. The hardness of the coatings may be related to the C content and the S/W ratio. A friction coe cient of 0.06–0.08 was achieved during sliding in ambient air by the coatings deposited in non-reactive mode with optimal C contents. The results indicate that sputtering in non-reactive mode should be the method of choice for synthesis of these coatings.